Let x 1 , x 2 , . . . , x 1 0 be the roots of the polynomial x 1 0 + x 9 + ⋯ + x + 1 . Find the value of n = 1 ∑ 1 0 1 − x n 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If x is a (non-real) root, then so is its complex conjugate x ˉ . Also, ∣ x ∣ = 1 since x is an 11th root of unity. We can conclude that 1 − x 1 + 1 − x ˉ 1 = 1 − x − x ˉ + x x ˉ 2 − x − x ˉ = 1 . Since there are five such conjugate pairs, the answer is 5 .
How did you get x to be an 11th root of unity? Could you please elaborate a little more. :)
f ( x ) ln ( f ( x ) ) d x d ln ( f ( x ) ) f ( x ) f ′ ( x ) n = 1 ∑ 1 0 1 − x n 1 = n = 1 ∏ 1 0 ( x − x n ) = ln ( n = 1 ∏ 1 0 ( x − x n ) ) = n = 1 ∑ 1 0 ln ( x − x n ) = d x d n = 1 ∑ 1 0 ln ( x − x n ) = n = 1 ∑ 1 0 x − x n 1 put x = 1 = f ( 1 ) f ′ ( 1 ) = Eleven 1 1 + 1 + ⋯ + 1 1 + 2 + ⋯ + 1 0 = 5
S = n = 1 ∑ 1 0 1 − x n 1 = ∏ n = 1 1 0 ( 1 − x n ) ∑ k = 1 1 0 ∏ n = 1 , n = k 1 0 ( 1 − x n ) = f ( 1 ) 1 0 n = 0 ∑ 9 ( − 1 ) n ( n 1 0 ) ( n 9 ) S n = 1 1 ∑ n = 0 9 ( − 1 ) n ( 1 0 − n ) S n = 1 1 ∑ n = 0 9 ( 1 0 − n ) = 1 1 ∑ n = 1 1 0 n = 1 1 2 1 0 ( 1 0 + 1 ) = 5 If f ( x ) = x 1 0 + x 9 + ⋯ + x + 1 = 0 ⟹ f ( x ) = n = 1 ∏ 1 0 ( x − x n ) where S n symmetric sums with S 0 = 1 (See note.) By Vieta;s formula S n = ( − 1 ) n (See reference)
Note that f ( x ) = x 1 0 + x 9 + ⋯ + x + 1 is such that ( x − 1 ) f ( x ) = x 1 1 − 1 , so that − x f ( 1 − x ) = ( 1 − x ) 1 1 − 1 , and hence x f ( 1 − x ) g ( x ) = f ( 1 − x ) = ( x − 1 ) 1 1 + 1 = j = 1 ∑ 1 1 ( j 1 1 ) ( − 1 ) 1 1 − j x j = j = 0 ∑ 1 0 ( − 1 ) 1 0 − j ( j + 1 1 1 ) x j = x 1 0 − ( 1 0 1 1 ) x 9 + ⋯ − ( 2 1 1 ) x + ( 1 1 1 ) and g ( x ) has roots 1 − x j for 1 ≤ j ≤ 1 0 . Thus we deduce that j = 1 ∑ 1 0 1 − x j 1 = ( 1 1 1 ) ( 2 1 1 ) = 5
Problem Loading...
Note Loading...
Set Loading...
Let y n = 1 − x n 1 , so x n = 1 − y n 1 . Therefore, since all of x 1 , x 2 , … , x 1 0 satisfy the equation 1 + x + x 2 ⋯ + x 1 0 = 0 , all of y 1 , y 2 , … , y 1 0 must satisfy the following equation:
1 + ( 1 − y 1 ) + ( 1 − y 1 ) 2 + ( 1 − y 1 ) 3 + ⋯ + ( 1 − y 1 ) 1 0 = 0
∴ + + + + 1 1 − y 1 1 − ( 1 2 ) y 1 + ( 2 2 ) y 2 1 1 − ( 1 3 ) y 1 + ( 2 3 ) y 2 1 − ( 3 3 ) y 3 1 ⋮ 1 − ( 1 1 0 ) y 1 + ( 2 1 0 ) y 2 1 − ( 3 1 0 ) y 3 1 + ⋯ + ( 1 0 1 0 ) y 1 0 1 = 0
∴ + + + + y 1 0 y 1 0 − y 9 y 1 0 − ( 1 2 ) y 9 + ( 2 2 ) y 8 y 1 0 − ( 1 3 ) y 9 + ( 2 3 ) y 8 − ( 3 3 ) y 7 ⋮ y 1 0 − ( 1 1 0 ) y 9 + ( 2 1 0 ) y 8 − ( 3 1 0 ) y 7 + ⋯ + ( 1 0 1 0 ) = 0
Now, by Vieta's formulas, the sum of the roots of this equation must be − a b , where a is the leading coefficient and b is the second coefficient. ∴ n = 0 ∑ 1 0 y n ∴ n = 0 ∑ 1 0 1 − x n 1 = − Eleven 1 ’s 1 + 1 + 1 + ⋯ + 1 − 1 − ( 1 2 ) − ( 1 3 ) − ( 1 4 ) − ⋯ − ( 1 1 0 ) = 1 1 1 + 2 + 3 + 4 + ⋯ + 1 0 = 2 × 1 1 1 0 ( 1 0 + 1 ) = 5